2022
DOI: 10.3389/fpsyg.2022.900417
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Emotion Regulation as Predictors of Teacher Burnout Among English as a Foreign Language Teachers: A Structural Equation Modeling Approach

Abstract: Since teachers and their psychological factors have a significant share of variance in accounting for success in educational contexts, significant number of empirical studies have investigated the associations among intrapsychic variables of teachers. To further examine the inter-connections between individual teacher constructs in English as a Foreign Language (EFL) contexts, this study explored the role of emotion regulation and teacher self-efficacy in predicting teacher burnout in the Chinese EFL context. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…In addition, the interpersonal relationship among social factors also has an important impact on self-efficacy. Bing et al (2022) confirmed that emotional regulation self-efficacy has a significant predictive effect on academic achievements. Buriæ and Macuka (2018) shows that there is a significant correlation between teachers’ emotions, self-efficacy, and work commitment.…”
Section: Introductionsupporting
confidence: 52%
“…In addition, the interpersonal relationship among social factors also has an important impact on self-efficacy. Bing et al (2022) confirmed that emotional regulation self-efficacy has a significant predictive effect on academic achievements. Buriæ and Macuka (2018) shows that there is a significant correlation between teachers’ emotions, self-efficacy, and work commitment.…”
Section: Introductionsupporting
confidence: 52%
“…So far, a plethora of investigations has been implemented on emotion regulation and its possible academic outcomes (e.g., Braun et al, 2020 ; Chang, 2020 ; Han et al, 2020 ; Bing et al, 2022 , among others). In their study, Han et al (2020) evaluated the effects of instructors’ emotion regulation on their well-being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing body of empirical work that is aiding the understanding of language teachers" psychological conditions and what can be done to support teachers. Additionally, by regulating and maintaining their emotion, it is also helps EFL teachers to overcome burnout (Bing et al, 2022). Moreover, when a teacher is future-oriented and optimistic in teaching, it will help to direct the learners" mindsets and positive growth of their language skills as they approach the language with a sense of optimism for the future and a developing sense of competence (Dornyei, 2005).…”
Section: Well-beingmentioning
confidence: 99%